2014
DOI: 10.1108/jat-12-2013-0035
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate talking pattern of an information support robot for people living with dementia: a case study

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:198285 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The category “Assistance” represent the largest group of articles encompassed in this systematic literature review. This category comprises 40 papers, gathering research from 2010 to 2017, and also in this case the overwhelming majority of the study took into consideration robots as the technology used: 26 out 40 papers (Granata et al, 2010, 2013; Gross et al, 2011, 2012; Wu et al, 2011, 2012, 2013, 2014, 2016; Pino et al, 2012, 2015; Seelye et al, 2012; Bruno et al, 2013; Schroeter et al, 2013; Nishiura et al, 2014; Pahl and Varadarajan, 2015; Agrigoroaie and Tapus, 2016, 2017; Broughton et al, 2016; Nakahara et al, 2016; Reppou et al, 2016; Bellotto et al, 2017; Darragh et al, 2017; Foukarakis et al, 2017; Korchut et al, 2017; Tsardoulias et al, 2017). The remaining papers are shared between two types of technology: namely, personal devices and wearable sensors, making up 14 out 40 papers (Mitseva et al, 2009; Martínez et al, 2011; Sacco et al, 2012; Diaz-Orueta et al, 2014; Meiland et al, 2014; Batista et al, 2015; König et al, 2015a; Lazarou et al, 2016; Mainetti et al, 2016, 2017; Vasileiadis et al, 2016; Kyriazakos et al, 2017; Mighali et al, 2017; Stavropoulos et al, 2017).…”
Section: Application 3: Assistancementioning
confidence: 99%
See 1 more Smart Citation
“…The category “Assistance” represent the largest group of articles encompassed in this systematic literature review. This category comprises 40 papers, gathering research from 2010 to 2017, and also in this case the overwhelming majority of the study took into consideration robots as the technology used: 26 out 40 papers (Granata et al, 2010, 2013; Gross et al, 2011, 2012; Wu et al, 2011, 2012, 2013, 2014, 2016; Pino et al, 2012, 2015; Seelye et al, 2012; Bruno et al, 2013; Schroeter et al, 2013; Nishiura et al, 2014; Pahl and Varadarajan, 2015; Agrigoroaie and Tapus, 2016, 2017; Broughton et al, 2016; Nakahara et al, 2016; Reppou et al, 2016; Bellotto et al, 2017; Darragh et al, 2017; Foukarakis et al, 2017; Korchut et al, 2017; Tsardoulias et al, 2017). The remaining papers are shared between two types of technology: namely, personal devices and wearable sensors, making up 14 out 40 papers (Mitseva et al, 2009; Martínez et al, 2011; Sacco et al, 2012; Diaz-Orueta et al, 2014; Meiland et al, 2014; Batista et al, 2015; König et al, 2015a; Lazarou et al, 2016; Mainetti et al, 2016, 2017; Vasileiadis et al, 2016; Kyriazakos et al, 2017; Mighali et al, 2017; Stavropoulos et al, 2017).…”
Section: Application 3: Assistancementioning
confidence: 99%
“…An example is offered by the work of Nishura et al The authors presented results from a report case study, in which a PaPeRo robot asked the participants to perform some daily activities, including taking medicines, measuring blood pressure, and cleaning up the room in three different ways for each task. Study results showed that the talking pattern changed the subjects' performances of daily activities (Nishiura et al, 2014). Another example is the study by Foukarakis et al in which the authors reported that, regarding the robot speech synthesis system, the users had difficulties understanding some phrases.…”
Section: Application 3: Assistancementioning
confidence: 99%
“…The most important finding in this study was that older people with attention deficit might make mistakes in their daily lives even though they are healthy older adults judged by cognitive assessment. We emphasized information should be repeated to enable people with lower attention to acquire correct information (Inoue et al, 2012;Nishiura et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…All participants received three experiment sessions (three days within one week) with all instruction patterns. The order of tasks and instruction patterns were selected randomly (Nishiura et al, 2014). Therefore, a total of nine data (3 tasks with 3 IPs) in each participant was taken.…”
Section: Methodsmentioning
confidence: 99%
“…If affirmative words are received, the information support will be terminated with the closing word ( Figure 3 ) [ 9 ]. A talking pattern allowed the older people to listen easily according to the characteristics of their cognitive impairment [ 39 ]. It was clear that the algorithm and talking pattern certainly allowed older people to obtain information.…”
Section: Methodsmentioning
confidence: 99%